(untitled) (Tribhuvan University Law Journal, 2025)
Always the definitional problem is attached with the concept of terrorism. One man’s terrorist is another man’s freedom fighter leads to the difficulty to all while defining the terrorism. Therefore, sometimes it becomes quite difficult to distinguish between terrorism and fight for the independence or freedom. Particularly, problem arise when the government or the establishment assume all those activities as terrorism which are against the interest of group capturing the power in the state or government. The same act becomes for another group a liberation movement. Terrorism always resulted in violence. The purpose of violence distinguishes any act whether such an act is terrorism or not. If the violence directed against the protected group of people and objects such a violence is terrorism under international humanitarian law. But, act of violence is directed against the combatant and military installations such an act may be considered military operation rather than the terrorism. Whether particular act is terrorism or not, depends upon the objective, nature and target of an act. 1991 UN General Assembly Resolution could be taken as an example. The Resolution denounced act of terrorism but, in virtually the same breath reaffirmed inalienable right to self-determination and independence of the people under colonial and racist and other forms of the alien domination and foreign occupation. This normative contradiction resulted in the criminalization of only specific acts such as aircraft hijacking, or attack against internationally protected persons under the various international treaties. Even because of definitional challenges, crime of terrorism was excluded from the ICC Statute.